Analisis Faktor-Faktor Yang Mempengaruhi Ketepatan Waktu Dalam Penyampaian Laporan Keuangan Pada Perusahaan Pertambangan Syariah Yang Terdaftar Di Bei Periode 2018-2020 - Syach Falah, Rifqi; Lubis, Fauzi Arif; Lubis, Arnida Wahyuni (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
This research aims to find empirical evidence about the factors that influence the timeliness of submitting financial reports for mining companies listed on the Indonesia Stock Exchange. The factors tested in this research are profitability, leverage, liquidity, company age as independent variables while timeliness is the dependent variable. The sample of this research consists of 39 companies listed on the Indonesia Stock Exchange (BEI) and have information regarding the date of submission of financial reports to Bapepam in the 2018-2020 period. Sample selection was carried out using the purposive sampling method. The data used is secondary data, obtained from the site www.idx.co.id. The data obtained was then tested using logistic regression analysis with a significance level of 5 percent. The research results identified that the variables profitability, leverage, had a positive and partially insignificant influence. Meanwhile, the variables liquidity and company age partially have a negative and insignificant influence on the timeliness of submitting financial reports for manufacturing companies listed on the Indonesia Stock Exchange. Meanwhile, tests carried out simultaneously (simultaneously) have an influence on the timeliness of submitting financial reports.